Inter-Religious Models and Criteria
XIII, 216 p.
Keywords: This book is a collection of papers presented and discussed at the 1992 Claremont Conference. Its contributing authors come from various disciplines that share a concern with models and criteria for inter-religious understanding, including religious studies, philosophy of religion, theology, comparative studies, and feminist philosophy.